2022
DOI: 10.3389/fgene.2022.886860
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of herbal medicines based on immune cell infiltration and immune- and ferroptosis-related gene expression levels to treat valvular atrial fibrillation

Abstract: Inflammatory immune response is apparently one of the determinants of progressive exacerbation of valvular atrial fibrillation(VAF). Ferroptosis, an iron-dependent modality of regulated cell death, is involved in the immune regulation of cardiovascular disease. However, the relevant regulatory mechanisms of immune infiltration and ferroptosis in VAF have been less studied. In the current study, a highly efficient system for screening immunity- and ferroptosis-related biomarkers and immunomodulatory ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…T cells follicular helper as a particular subset of T cells is essential for germinal center formation, differentiation, and maturation of B cells (45). This sort of T cells was found to promote a chronic cardiac inflammatory response by enhancing the function of B cells in AF (46). In accordance with the present finding, another bioinformatics study also performed the immune infiltration analyses and found the downregulation of T cells follicular helper in AF compared with healthy subjects (47).…”
Section: Discussionsupporting
confidence: 88%
“…T cells follicular helper as a particular subset of T cells is essential for germinal center formation, differentiation, and maturation of B cells (45). This sort of T cells was found to promote a chronic cardiac inflammatory response by enhancing the function of B cells in AF (46). In accordance with the present finding, another bioinformatics study also performed the immune infiltration analyses and found the downregulation of T cells follicular helper in AF compared with healthy subjects (47).…”
Section: Discussionsupporting
confidence: 88%
“…The presence of systemic inflammation in VAF patients was found by either histopathological examination of the left atrium or by measuring serum inflammatory biomarkers. In local cardiac tissue, VAF patients exhibited higher infiltration of neutrophils and resting stage dendritic cells, while those with sinus rhythm exhibited higher infiltration of follicular helper T cells [ 16 ]. Neutrophil-mediated inflammatory responses were mainly associated with neutrophil extracellular traps that recruited other inflammatory cells such as macrophages to amplify the inflammatory response and promoted collagen synthesis leading to fibrosis.…”
Section: Discussionmentioning
confidence: 99%